Analysis of the Causes of Science Learning Difficulties for Elementary School Students - Ika Putra Viratama; Prihaten Maskhuliah (Universitas Muhammadiyah Enrekang, 2023)
Education is an important thing that every nation tries to achieve development. The more meaningful a nation becomes, the more it continues to have a positive impact on the development of the nation and its country. This research aims to analyze the causes of difficulties in teaching students science in elementary schools. This research is literature review research using the Pubmed database and the Google Scholar search engine. The results obtained were 10 articles that were similar to the inclusion and exclusion criteria. The research results found 6 themes, namely physiological, psychological, social, facilities and infrastructure, learning procedures, and teachers. The implication for science learning in elementary schools should be to open up opportunities to increase students' scientific curiosity. But the fact is that not all students understand the competencies as expected. The lack of ability to design science is caused by students' difficulties in responding to the learning given by their teachers.